The Loss of Reason and the Task of Education - Enrico Bottero (University of Bologna, 2020)
Democracy is not just a set of rules and procedures. Today, through a clever use of analogical and digital technologies, increasing invasive consumerism can erode two attitudes of the citizen: the deep attention and the construction of the symbolic world. Actually, for the consumer conditioned by the drive to buy, reflective thinking is only an obstacle. Education, in particular in the school, cannot renounce the formation of thought. For this reason it is important to rehabilitate rituals, albeit in new forms, in order to form the ability to wait. It is also important to train to the pleasure of learning instead of pleasure of success. The pleasure of learning is the premise for being able to cultivate humanistic and scientific knowledge and through them, enrich one's own symbolic world.